QTL Study to Reveal Soybean Response on Abiotic and Biotic Stresses - Puji Lestari; Sutrisno Sutrisno; I Made Tasma (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2014)
As an important grain legume, the improved soybean(Glycine max [L.] Merr.) adaptive to environmental changesis a valuable genetic resource. Strategy to minimize theimpact of climate effects should be underlined on soybeanproduction encompassing advanced genomics and wellpredicted future climate. Crops including soybean respondto climate change in the aspect of abiotic and bioticenvironmental factors. To predict soybean response toabiotic and biotic stresses, current progress of quantitativetrait loci (QTL) for abiotic and biotic stresses and floweringand related genomic resources could be accessed atSoyBase (http://www.soybase.org) and Phytozome(http://www.phytozome.net). As the involvement of abioticand biotic stresses modulating flowering in soybean, geneslinked to QTL for abiotic/biotic stress and flowering/maturitywere also potential for resisting the environmental changes.By mapping QTLs for flowering using one population indifferent locations (Korea and China) with distinctivelongitude, latitude, and altitude, syntenic correlationbetween these two QTLs on soybean chromosomes 6 and13 indicates the environmental specific role of syntenicregions. The information on QTL and related candidategenes may assist marker-assisted breeding and enactsoybean as a model of adaptive legume crop under abiotic/biotic stress.